A Case Study of Variety of Alay Language toward Shemale in Pucuk - Iib Marzuqi; Laila Tri Lestari; Lina Nurul Hidayati; Inti Khobatsaniyah; Krisna Andika (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2020)
This study aims to describe the vocabulary, sound changes and factors influence the use of the Alay language by shemale in Pucuk. This research was conducted in Pucuk with the subjects were shemale in Pucuk. Data showed 67 obtained Alay language vocabularies used by shemale in Pucuk. Vocabulary structure and sound changes in Alay language among shemale in Pucuk are addition of phonemes, omission of phonemes, shortening, use of other terms, replacement of letters, combinations of capital and lowercase letters, combinations of letters and numbers, combinations of letters, numbers, symbols, and abbreviations. The factors that influence the use of Alay language vocabulary by shemale in Pucuk are Alay language is considered a medium of expression, a factor that arises from within a shemale aims to be pampered was that a sense of eager to be noticed, the language used seems more slang and modern, For shemale, Alay language can understand their condition, they are more comfortable using the Alay language. It is modern and fun language to use as a trick and attraction for their own, and surroundings, such as friends, television.